D-dimer as a predictor of severity and outcome in acute pancreatitis - Joseph A; Harikrishnan CP; Oommen AN; Nair A (Journal of Medical and Scientific Research)
This prospective observational study, conducted at Jubilee Mission Medical College and Research Institute, Thrissur, explored the role of D-dimer as a predictive marker for the severity and outcomes of acute pancreatitis. A total of 60 patients diagnosed through clinical, biochemical, and imaging criteria were included. The study demonstrated a significant correlation between elevated D-dimer levels and the severity of acute pancreatitis, classified according to the Atlanta criteria. Specifically, D-dimer levels ≥2528 ng/L were strongly associated with severe acute pancreatitis (SAP), while levels ≤1871 ng/L were primarily linked to mild cases. The study identified a D-dimer cutoff value of 1871 ng/L as an effective predictor of complications, with an area under the curve (AUC) of 0.870, yielding 87.5% sensitivity, 83.3% specificity, a positive predictive value of 77.78%, a negative predictive value of 90.90%, and 85% overall accuracy. In addition to severity prediction, the study examined the association between D-dimer levels and the need for supportive interventions. These findings suggest that D-dimer is a valuable biomarker for early risk stratification and could aid in guiding therapeutic decisions in the management of acute pancreatitis. The study emphasizes the importance of conducting larger, multi-center trials to validate these findings and to better understand the prognostic value of D-dimer in diverse clinical settings, potentially enhancing early diagnosis and personalized treatment strategies for patients with acute pancreatitis.